RANKINGS UNIVERSITÁRIOS MUNDIAIS: ANÁLISE DA CONGRUÊNCIA ENTRE OBJETIVOS E INDICADORES - Sandra Mara Iesbik Valmorbida (Universidade Federal de Santa Catarina, 2018)
The international character of higher education takes students, universities and governments have a growing interest in knowing the position of universities compared to others in the global context. The rankings are attractive as they provide this information. However, each of the rankings developed makes use of indicators and metrics of measurement defined according to the purpose for which it was created. This work aims to investigate, based on scientific publications, if there is congruence between the indicators used by university rankings with the objectives for which the ranking was developed. For this search was conducted for scientific articles in web basis of Science and SCOPUS, which resulted in 25 articles were then examined. This is a bibliographic research, qualitative in nature, based on secondary data. So, first we identified the rankings presented by the work, and only analyzed those who appeared in four or more jobs: ARWU; THES; HEEACT; CWTS; Webometrics; SCImago; QS; America's Best College. Based on the analysis, it was found that the analyzed rankings, which presented their indicators, all present alignment of indicators and targets, although some cases are generic and superficial way.